Ultrasonic Synthesis and Anti-Microbial Screening of Some 1, 3, 4-Thiadiazole Derivatives - Mustafa K. Shneshil (Journal of Global Pharma Technology, 2018)
Some novel1,3,4-thiadiazole derivatives (1a-10a) were greenly synthesized by the reaction of substituted benzoic acid with thiosemicarbazide in the presence of phosphorus ox chloride (POCl3) under ultrasonic irradiation forming2-substituted phenyl-5-amino-1,3,4-thiadiazole (1-10). The later were reacted with benzoyl chloride under Schotten-Baumann conditions to give the target molecule 2-substituted phenyl-5(N-benzoyl)-amino-1, 3, 4-thiadiazole (1a-10a). The structures of the compounds synthesized identified by using spectral analysis methods (F.T-IR, 1H-NMR and13C-NMR). The compounds (1a-10a) screened for anti-microbial (Staphylococcus aureus, Staphylococcus epidermidis, Micrococcus luteus, Bacillus cereus, Escherichia coli, and Pseudomonas aeruginosa) activities using disc diffusion method. The minimum inhibitory concentrations (MICs) of the compounds also calculated by agar streak dilution Method the compounds (1a and 5a) were the most active compounds against the above strains of microbes.Keywords: Green chemistry, Ultrasonic, 1, 3, 4-Thiadiazole, Amide, Anti-microbial.